2011
DOI: 10.2174/156800911795538048
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Peptides and Lung Cancer

Abstract: Lung cancer is a leading cause of death in both men and women, with over 1,000,000 new cases diagnosed worldwide annually and a 5-year survival rate of only 14%, a figure that has improved little in the past thirty years. This poor prognosis suggests a need for novel approaches for the treatment and prevention of lung cancer. The renin-angiotensin system is an established, primary regulator of blood pressure, homeostasis, and natriuresis; however, compelling evidence indicates that the angiotensin peptides als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 89 publications
2
50
0
Order By: Relevance
“…Physiologically, ACEs degrade angiotensin-I (AT-I) to generate AT-II, which results in hypertension, and to participate in the degradation of bradykinin and the heptapeptide Ang-(1-7). 36 Given as therapy for hypertension, heart failure, and diabetic nephropathy, ACEIs suppress ACE, reduce the production of AT-II, and indirectly block the type 1 and type 2 receptors of AT-II, whereas ARBs selectively block the action of the AT-II type 1 receptor. 37 In vitro and in vivo studies have shown that ACEIs and ARBs suppress tumor growth, tumor-associated angiogenesis, and metastasis, but these effects have not led to improvements in survival in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, ACEs degrade angiotensin-I (AT-I) to generate AT-II, which results in hypertension, and to participate in the degradation of bradykinin and the heptapeptide Ang-(1-7). 36 Given as therapy for hypertension, heart failure, and diabetic nephropathy, ACEIs suppress ACE, reduce the production of AT-II, and indirectly block the type 1 and type 2 receptors of AT-II, whereas ARBs selectively block the action of the AT-II type 1 receptor. 37 In vitro and in vivo studies have shown that ACEIs and ARBs suppress tumor growth, tumor-associated angiogenesis, and metastasis, but these effects have not led to improvements in survival in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…In the opposite, Ang-(1-7), the specific agonist of Mas, has been described to have antitumor activities, which could even be therapeutically exploited (Gallagher et al, 2011). The tumorigenic and proproliferative actions of Mas and maybe also the other Mrgprs may only be observed above a certain threshold of overexpression in cells which is normally not reached in vivo.…”
Section: Mas-related G Protein-coupled Receptors In Tumorsmentioning
confidence: 99%
“…Several studies support the significant association of AGTR2 signaling with various types of cancer (renal, colorectal, prostate, uterine, breast and pancreatic) [7,21,22,23,24,25]. Initially, the 2 AGTR2 SNPs studied here were only associated with the circulatory system or with metabolism and nutrition disorders [26].…”
Section: Discussionmentioning
confidence: 71%